เปรียบเทียบผลการตอบสนองต่อการออกกำลังด้วยการเดินสายพานโดยฟังเพลงไทยและไม่ฟังเพลงในประชากรที่ไม่ได้ออกกำลังกายเป็นประจำ: เปรียบเทียบผลการตอบสนองต่อการออกกำลังด้วยการเดินสายพานโดยฟังเพลงไทยและไม่ฟังเพลงในประชากรที่ไม่ได้ออกกำลังกายเป็นประจำ - แรงกล้า สริสสา; เดชะรินทร์ ปวีณ์สุดา; แจ่มไพบูลย์ จิรภา (ASEAN Journal of Rehabilitation Medicine, 2017)
Objectives: To compare perceived exertion and physiological responses during treadmill walking between listening to Thai music and no music in untrained adults. Study design: Assessor blinded, crossover, randomized control trial. Setting: Department of Rehabilitation Medicine, King Chulalongkorn Memorial Hospital Subjects: Untrained healthy volunteers aged 18-59 years Methods: Participants were assessed baseline data (age, weight, height, heart rate, blood pressure) then randomized into 2 groups. First group listen to Thai contemporary music selected from four types of music (Thai pop, Looktung, Lookkrung and Peuchevit) while performing treadmill exercise at 60% HRmax for 20 minutes, washout 1 week then performed treadmill exercise again without listening to music. Second group the order was reversed. RPE, SBP, maximum speed, total distant and enjoyment VAS were recorded for each exercise session. Results: 30 volunteers, 13 males and 17 females were recruited. 2 males dropped out, one from each group. Mean RPE was significantly lower listening to music (11.29) comparing with no music (12.37, p < 0.001). Mean enjoyment VAS was significantly greater while listening to music (6.92) comparing with no music (4.37, p<0.001). No statistically significant difference regarding SBP, speed and total distant. Conclusion: Music can decrease RPE and increase enjoyment during treadmill exercise at fixed work load.